8th International Conference on University Teaching and Innovation (CIDUI): Flexible Training Models - CIDUI organising Comittee (OmniaScience, 2015)
The Organising Committee of the 8th International Conference on University Teaching and Innovation (CIDUI) wishes to thank the Editorial Board of the Journal of Technology and Science Education (JOTSE) for publishing this special issue. Since the year 2000, a new CIDUI conference has been held every two years. Today, it is a well-established event that provides an opportunity to share advances and innovation in the field of higher education.